Assessing the Compliance of Online Marketplace Mechanism with Shari’ah Law (Case Study of Bukalapak) - Masputra, Iryandi; Akbar, Nashr (AL-IKTISAB: Journal of Islamic Economic Law, 2017)
Bukalapak is one of the biggest online marketplace in Indonesia. Bukalapak provides a place for trading for sellers and buyers, utilizing the applications on the internet as a space to trade. The objective of the study is to assess the the compliance of product, buyer and seller verification system, payment and delivery transaction system of Bukalapak with the Shariah law. This research uses a qualitative approach; interview and observation. The collected data will be analysed with interactive analysis model by Miles and Huberman. The result of this study shows that as an online marketplace, Bukalapak complies with the legal standards of Shariah law which is based on ijab qabul between the seller and the buyer, also there is a form of liability or indemnity imposed by Bukalapak with the view of balance and fairness between all Bukalapak users. The result also shows that Bukalapak had been running based on honesty and openness so that it is able to develop the market based on Islamic economics. Hence, it earns the trust from the sellers and the buyers as a place for buying and selling.